White matter alterations in antipsychotic- and mood stabilizer-naive individuals with bipolar II/NOS disorder. - Yip, S; Chandler, R; Rogers, R; Mackay, C; Goodwin, G (2013)
Structural magnetic resonance imaging (MRI) studies using voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) have been inconsistent in demonstrating impairments in gray matter (GM) and white matter (WM) structures in bipolar disorder (BD). This may be a consequence of significant confounding effects of medication, illness history and selection of controls in existing studies. Study of bipolar II or not-otherwise-specified (BD II/NOS) disorder provides a solution to these confounds and a bridge to unipolar cases across the affective spectrum. Thirty-eight euthymic, antipsychotic- and mood stabilizer-naïve young adults (mean age = 20.9 years) with BD II/NOS and 37 age-, cognitive ability- and gender-matched healthy controls (HCs) underwent MRI. Voxel-wise and regional gray matter volume comparisons were conducted using voxel-based morphometry (VBM). Tract-based spatial statistics (TBSS) were used to assess whole-brain WM, as indexed using fractional anisotropy (FA), mean diffusivity (MD), parallel and perpendicular diffusion values. No between-group differences were observed for whole-brain VBM comparisons. By contrast, in comparison to HCs, participants with BD II/NOS had significant widespread reductions in FA and increased MD and perpendicular diffusion values in virtually all the major cortical white matter tracts. These data suggest pathophysiological involvement of WM microstructures - but not GM macrostructures - in high functioning BD II/NOS patients at an early age and before significant clinical adversity has been recorded. We propose that white matter development is a valid candidate target for understanding genetic and environmental antecedents to bipolar disorder and mood disorder more generally.